The effects of the social hierarchy destabilization on the foraging activity of eusocial wasp Mischocyttarus cerberus styx Richards, 1940 (Hymenoptera: Vespidae: Polistinae) - Conceição Costa Filho, Vanderlei [UNESP] (2011)
The genus Mischocyttarus comprises 245 species of neotropical basal eusocial wasps. They form small colonies (rarely more than few tens of individuals); castes are morphologically undifferentiated and determined behaviorally by agonistic interactions. The aim of this study was to verify the effects of the experimental disruption of social hierarchy on foraging activity of Mischocyttarus cerberus styx. We observed six colonies in postemergence phase and recorded data on the foraging activity under two experimental conditions: (1) removal of lower-ranked females and (2) removal of higher ranked females, except the queen. Our results showed that the removal of higher-ranked females had higher effect on the number of foraging trips of M. cerberus styx than the removal of lower-ranked females (the number of foraging trips/hour decreased by 66.4 and 32.7, resp.). Such results are likely due to the social organization of this species and the presence of a distinct class of females, which in this study were regarded as intermediates. Our data also showed that, irrespective of the hierarchical status of the females, the removal of two or three individuals affected significantly the number of foraging trips in this species. Copyright 2011 Vanderlei Conceio Costa Filho et al.